Aligning AfCFTA and CAADP for Africa’s agrifood systems future - Omamo, Steven Were; Ulimwengu, John M.; Traoré, Fousseini; Piñeiro, Valeria; Hill, Ruth Vargas (International Food Policy Research Institute, 2025)
Key messages AfCFTA and CAADP are Africa’s twin engines for structural transformation, but their success depends on deliberate alignment. While AfCFTA drives regional integration through trade liberalization, CAADP focuses on building resilient, inclusive, and sustainable agrifood systems. • There is strong strategic complementarity between the two frameworks, especially in goals related to competitiveness, private sector development, and integration of regional value chains. But alignment weakens at the level of implementation—risking policy incoherence and missed opportunities. • Tensions between AfCFTA and CAADP implementation exist around tariff liberalization, domestic policy space, and sector readiness, with risks that liberalized trade could outpace capacity of fragile agriculture sectors to compete, adapt, and benefit. • Food security, equity, and environmental resilience—central to CAADP—are recognized in AfCFTA objectives and justify certain exceptions yet remain only weakly embedded in its implementation protocols. • Institutional silos and fragmented infrastructure strategies could undermine coherence, with risks of trade and agriculture ministries, as well as regional and continental bodies, operating separately. • Strategic coordination, sequencing, and governance reform are essential. Alignment of AfCFTA and CAADP is not automatic—it must be designed, negotiated, and sustained to deliver on Africa’s transformation promise. • Bridging AfCFTA and CAADP is not a one-time alignment exercise but rather a strategic process of political, institutional, and analytical interaction that must be continuously revisited and actively managed if it is to deliver on the continent’s shared aspirations for prosperity, food security, and sustainability.